Analisis Kelayakan Usahatani Kacang Panjang di Desa Teteona Kecamatan Wonggeduku Barat Kabupaten Konawe - Leni Saleh; Sarty Syarbiah; Milawati Saranani; Astina Astina; Devi Ayu Anggraeni (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
The aim is to determine the feasibility of long bean farming in Tetona Village, Wonggeduku District, Konawe Regency. In this study, 30 respondents were used with the census method, namely making all existing populations as respondents. The data analysis used in this study was a business feasibility analysis. The income obtained by long bean farmers in Polandangi Village, Wonggeduku District, Konawe Regency was IDR 19,268,785/Ha for one planting season. From the calculation above, it was found that the R/C value of long bean farming is 1.9. This shows that the R/C value of 1.9> 1, meaning that if farmers spend IDR 1, then farmers will get an income of IDR 1.9 and long bean farming in the research area is feasible.